Wavelet analysis of the ECG signals for three common heart diseases in Jordan - Chebil, Jalel; Al Nabulsi, Jamal (IIUM Press, 2011)

(untitled)
The electrocardiogram is a common diagnostic tool used to monitor heart activity and can provide information about the cardiovascular problems. An automatic detection of the ECG traces can be valuable aid in the diagnosis process. The wavelet transform has proven to be an important tool in the analysis of biomedical signals, and the ECG in particular. This paper proposes a method for the classification of various types of ECG signals using wavelet transform. The method is developed based on the ECG data collected at different local hospitals in Jordan. The data include normal ECG records from healthy people and abnormal ECG signals taken from patients with common heart diseases in Jordan such as right atrial hypertrophy, left atrial hypertrophy and hypocalcaemia